Evaluation of the effectiveness of an interactive avatar‐based education application for improving heart failure patients' knowledge and self‐care behaviours: A pragmatic randomized controlled trial protocol. (30th July 2018) - Wonggom, Parichat; Du, Huiyun; Clark, Robyn A.
Abstract: Aim: The aim of this study was to evaluate the effectiveness of an avatar‐based education application for improving knowledge and self‐care behaviour in patients with heart failure (HF). Background: Avatar‐based technologies for supporting education are an innovative approach for patients with low literacy, low health literacy and English as a second language. The use of avatar technologies for patient education has shown benefits in improving knowledge, self‐care behaviours and quality of life in chronic diseases such as cancer, diabetes and depression. Research has demonstrated positive outcomes in clinical practice. However, the effectiveness of this technology has not been evaluated among patients with HF. Design: A multi‐centred, non‐blinded randomized, two‐armed parallel pragmatic, controlled trial. Method: Eighty‐eight participants will be recruited from the HF clinics at three public hospitals and randomized into either control or intervention groups. The intervention group will receive the avatar‐based education plus usual care. The control group will receive usual care. The primary outcome is HF knowledge, secondary outcomes include; improved self‐care behaviours, readmission and satisfaction. Data will be collected at the baseline and at 1‐ and 3‐month follow‐ups. Discussion: This study will measure the effectiveness of avatar‐based education on patients' knowledge and self‐care behaviours following HF. The evidence will be evaluated in terms of the reduction in patients' readmission. Abstract : 目标: 本研究旨在评估提高心力衰竭患者知识和自我管理行为的虚拟化身型教育应用的有效性。 背景: 支持教育的虚拟化身技术对于读写能力低下、健康素养低下并将英语作为第二语言的患者而言, 是一种创新方法。利用虚拟化身技术进行患者教育已显示出提高患者关于癌症、糖尿病和抑郁症等慢性病的知识、自我管理行为和生活质量方面的益处。研究表明, 已在临床实践中取得了积极成果。然而, 尚未在心力衰竭患者中评估该技术的有效性。 设计: 多中心非盲随机双臂平行实用型对照试验。 方法: 将从三家公立医院的心力衰竭门诊部招募88位受试者, 并将其随机分配到对照组和干预组。干预组将接受虚拟化身型教育和常规护理;而对照组将仅接受常规护理。本研究主要希望获得相关知识, 另外希望获得包括经改善自我管理行为、再入院和满意度方面的经验。数据收集将在基线建立、随访期第一个月和第三个月时进行。 讨论: 本研究将衡量虚拟化身型教育对心力衰竭患者的知识和自我管理行为的有效性, 并将根据患者再入院数量的减少来评估相关迹象。